2009
DOI: 10.1016/j.febslet.2009.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adipocyte differentiation by RORα

Abstract: a b s t r a c tHere we show that gene expression of the nuclear receptor RORa is induced during adipogenesis, with RORa4 being the most abundantly expressed isoform in human and murine adipose tissue. Over-expression of RORa4 in 3T3-L1 cells impairs adipogenesis as shown by the decreased expression of adipogenic markers and lipid accumulation, accompanied by decreased free fatty acid and glucose uptake. By contrast, mouse embryonic fibroblasts from staggerer mice, which carry a mutation in the RORa gene, diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
4
34
1
Order By: Relevance
“…Furthermore, sg/sg mice display reduced adiposity, increased metabolic rate, improved insulin sensitivity, resistance to diet-induced obesity, and hepatic steatosis (17,18). However, studies utilizing either 3T3-L1 cells or sg/sg MEF cells have indicated a contrary role whereby attenuation of Ror␣ enhanced adipogenesis (11,30). Therefore, we investigated overall body composition and adi-posity [by dual-energy X-ray absorptiometry (DEXA) and MRI] and then analyzed adipose tissue samples [by quantative PCR (qPCR) and Western blotting], comparing sg/sg mice with their wild-type (WT) counterparts.…”
mentioning
confidence: 98%
“…Furthermore, sg/sg mice display reduced adiposity, increased metabolic rate, improved insulin sensitivity, resistance to diet-induced obesity, and hepatic steatosis (17,18). However, studies utilizing either 3T3-L1 cells or sg/sg MEF cells have indicated a contrary role whereby attenuation of Ror␣ enhanced adipogenesis (11,30). Therefore, we investigated overall body composition and adi-posity [by dual-energy X-ray absorptiometry (DEXA) and MRI] and then analyzed adipose tissue samples [by quantative PCR (qPCR) and Western blotting], comparing sg/sg mice with their wild-type (WT) counterparts.…”
mentioning
confidence: 98%
“…ROR␣ overexpression in 3T3L1 cells also blocks the adipogenic process. 52 Interestingly, REV-ERB␣ regulates this process in a subtle manner because the REV-ERB␣ protein must increase and then decrease to allow proper differentiation of fibroblasts into mature adipocytes. 53,54 Human data are still scarce.…”
Section: Duez and Staels Circadian Metabolic Control By Nuclear Recepmentioning
confidence: 99%
“…26), could be due to a diminished deposition of TG in adipose tissue under fasting conditions. Indeed, reduced adiposity was not described to be linked to a defect of adipogenesis, which, on the contrary, was found to be improved (12,35), nor to an altered lipolysis [observation based on the gene expression of two major lipolytic enzymes, hormone-sensitive lipase (HSL) and adipose triglyceride lipase (ATGL) (26)]. We confirmed that ROR sg/sg mice exhibited no clear defect in lipogenesis under feeding conditions on the basis of similar sterol regulatory element-binding protein-1c (SREBP)-1c, PPAR␥, or fatty acid-binding protein 4 mRNA amount in inguinal fat (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…1) This pathway shares with liver gluconeogenesis the same key gene, PCK1; 2) previously, we revealed that GOT1, encoding aspartate aminotransferase, another enzyme involved in glyceroneogenesis, was an in vitro ROR␣ target gene (45); and 3) ROR sg/sg mouse, a natural mutant ROR␣-deficient strain (13), exhibits a lean phenotype with decreased fat mass and small adipocytes for an unsolved reason (26). Indeed, adipocyte precursors from these mice are fully competent to differentiate in vitro (12,35). This raised the possibility that ROR sg/sg mice could harbor specific adipose defects that limit their capacity for energy storage.…”
mentioning
confidence: 99%